Analysis of Tourist Typologies and Motivations in Urban Heritage Precincts: The Philosophical Axis of Yogyakarta - Andjanie, Isabella Fitria; Annisa, Lintang; Harahap, Agustian; Pratiwi, Wiwik Dwi (Jurnal Pariwisata Terapan, 2023)
Understanding tourist typologies and motivations is crucial for developing efficient tourism products and strategies in urban heritage precincts. Different tourist typologies have unique travel patterns that influence their tendencies and behavior in urban tourism areas. Similarly, tourist motivations affect their preferences for regional attractions and activities. By comprehending tourist typologies and motivations, urban heritage precincts can design tailored marketing strategies and activities catering to diverse tourist types and demands. This study aims to determine the characteristics of tourists visiting the Yogyakarta Philosophical Axis precinct, including their typology and motivation. The methodology involved distributing questionnaires to tourists at various attractions in the Philosophical Axis precinct, and quantitative statistical analysis was performed on the collected data. Based on the processed results of questionnaire data on domestic tourist, the findings reveal that tourists visiting Philosophical Axis fall into three categories: sampler, browser, and explorer, with differences in age range, preferences, and movement distribution patterns. Additionally, there are diverse motivations for tourists visiting the Philosophical Axis precinct, indicating that several activities and experiences can attract tourists to the region. The results of this study also recommend some approaches to optimize tourism planning and management in urban areas tailored to tourists' typology and motivation.